746 Non small-cell lung cancer cells and cancer-associated fibroblasts drive macrophage polarization in a novel co-culture model. (9th November 2020) - Flaming, Josiah; Chandra, Raghav; Girard, Luc; Ganguly, Debolina; Toombs, Jason; Minna, John; Brekken, Rolf
Abstract : Background: The plasticity of macrophage phenotype within the tumor microenvironment (TME) correlates with prognosis in non-small cell lung cancer (NSCLC). 1 M2-like macrophages promote immunosuppression and facilitate tumor progression, while M1-like macrophages may drive an inflammatory antitumor immune response. 2 Through a novel co-culture model comprised of cancer cells, cancer-associated fibroblasts (CAFs), and macrophages, we investigated whether NSCLC oncogenotype impacts macrophage phenotype and postulated that the immunosuppressive activity of macrophages is mediated through tumor-secreted soluble molecules. If identified and inhibited, these may re-sensitize cancer cells to immune surveillance and enhance antitumor immunity. Methods: We developed an in vitro co-culture system (patient-derived NSCLC cells, human CAFs, and mouse macrophages) to interrogate impact of NSCLC cells and CAFs on macrophage phenotype. Expression of salient macrophage genes (i.e. ARG1, NOS2, IL-1β, IL-6, CHIL-3, SOCS3) was investigated through species-specific qPCR. Whole-genome RNA sequencing (RNAseq) in select cases was conducted and cytokine arrays measuring expression of 40 inflammatory cytokines were performed. Positive controls included stimulation of macrophages with LPS and IL-4. Results: More than 70 NSCLC cell lines were characterized in the co-culture assay. Three highly reproducible clusters of macrophage phenotypes were identified: high Arginase (immunosuppressive), high IL-1β (inflammatory) and high SOCS3 (inflammatory, involved in JAK-STAT3 pathway) (figure 1 ). 3 4 Major oncogenotypes (i.e. KRAS, TP53, STK11, EGFR, BRAF mutation) did not correlate with macrophage phenotype (figure 2 ). Analyses of differences between the 3 clusters is ongoing. 10 exemplar NSCLC lines representing each of these 3 clusters were selected for RNA sequencing (mouse genes) and cytokine array protein (human) profiling. Across all clusters, we found suppression of macrophage endocytosis pathways and activation of scavenger receptor A (SRA) signaling, reflecting an M2-like phenotype. 5 We also observed increased expression of human IL-6, IL-8, and MCP1, which are implicated in suppression of innate immune sensing of tumor cells (figure 3 ). RNAseq of CAF lines demonstrated mixed inflammatory and myofibroblastic phenotypes (figure 4 ), with increased expression of genes associated with macrophage recruitment and activation including: IL-6, CSF-1, CXCL6, CCL2, and CCL7. 6 Conclusions: Through this novel co-culture model (figure 5 ), we demonstrate that patient-derived NSCLC cells reproducibly induce three major macrophage phenotypes in an oncotype-independent manner. Furthermore, cytokine release from NSCLC cells and CAFs is implicated in this process. This co-culture model provides a physiologically consistent experimental platform to identify tumor cell and CAF features that drive macrophage phenotype which may be suitable for targeted therapy. Acknowledgements: We thank the McDermott Center Next-Generation Sequencing Core at UT Southwestern. Figure 5 was created with Biorender.com References: Sumitomo R, Hirai T, Fujita M, et al. M2 tumor associated macrophages promote tumor progression in non small cell lung cancer. Exp Ther Med 2019 Dec 1;18(6):4490–8. Chen Y, Song Y, Du W, et al. Tumor-associated macrophages: an accomplice in solid tumor progression. J. Biomed. Sci 2019 Dec;26(1):1–3. Orecchioni M, Ghosheh Y, Pramod A, et al. Macrophage polarization: different gene signatures in M1 (LPS+) vs. classically and M2 (LPS–) vs. alternatively activated macrophages. Front. Immunol 2019 May 24;10 :1084. Wilson HM. SOCS proteins in macrophage polarization and function. Front. Immunol 2014 Jul 28;5 :357. Sun Y, Xu S. Tumor-associated CD204-positive macrophage is a prognostic marker in clinical stage I lung adenocarcinoma. Biomed Res. Int 2018 Jan 1;2018. O'Hayre M, Salanga C, Handel T, et al. Chemokines and cancer: migration, intracellular signalling and intercellular communication in the microenvironment. Biochem. J 2008 Feb 1;409(3):635–49